Infection Control - Timothy Dellit; Estella Whimbey (Association of American Medical Colleges, 2010)
Abstract Infection Control is a vital part of patient safety concerned with the prevention of health care-associated infections and the transmission of infectious agents among patients and health care workers. Every year, there are 2 million health care-associated infections in this country responsible for 90,000 deaths. The emergence of multidrug-resistant organisms such as methicillin-resistant Staphylococcus aureus, vancomycin-resistant enterococci, and Acinetobacter has been associated with increased patient morbidity and mortality, increased length of stay, and increased health care costs. Fundamental infection control measures such as hand hygiene, respiratory hygiene, standard and transmission based precautions, aseptic techniques, and immunization against vaccine-preventable diseases play a significant role in preventing the transmission of infectious agents within the health care setting. The rates of completing the curriculum by incoming residents and fellows were 86% in 2008 (n = 348) and 82% in 2009 (n = 357). Learner evaluations of the curriculum have been favorable. Eighty-five percent of those surveyed said the content presented was well organized and easy to understand; 85% said the content clearly pointed out key clinical implications; 86% agreed that the questions and cases helped reinforce learning; and 83% agreed the material presented is relevant to clinical practice. As a result of completing the module; 79% felt confident in incorporating patient safety principles in patient care; 82% felt the training module was easy to navigate; and 81% felt that interacting with multimedia components in the programs was easy.